A Simple Model of Monetary Pollicy and Currency Crises - Philippe Aghion; Philippe Bacchetta; Abhijit Banerjee (Swiss National Bank, Study Center Gerzensee, 1999)
This paper analyzes the optimal interest rate policy in currency crises. Firms are credit constrained and have debt in domestic and foreign currency, a situation that may easily lead to a currency crisis. An interest rate increase has an ambiguous effect on firms since it both makes more difficult to borrow and may decrease the foreign currency debt burden. In some cases it is actually best to decrease the interest rate. We also show how these issues are related to development of the financial system.
Keywords: 330; Geldpolitik; Währungskrise; Wirtschaftsmodell; Theorie